Psychomythology of Psychopathology: Myths and Mythbusting in Teaching Abnormal Psychology. (January 2023) - Curtis, Drew A.; Kelley, Leslie J.
Background: A great amount of information is presented to psychology students through various mediums, often leading to misinformation and believing inaccurate psychological myths. Objective: We conducted two studies to examine psychomythology of psychopathology and whether mythbusting may be an effective pedagogical tool. Method: In Study 1, a total of 251 participants were recruited and asked about psychology myths they believed by using the Myths of Abnormal Psychology Questionnaire (MAP). In Study 2, a total of 46 students across two sections of abnormal psychology courses were asked about psychological myths they believed at the onset of class and at the end of class using the MAP. These students also were provided with an educational mythbusting intervention throughout the class. Results: Participants endorsed several myths of psychopathology and indicated that the greatest sources of their understanding came from instructors, the internet, movies, and mythbusting led to a decrease in myth endorsement. Conclusion: Students enter abnormal psychology courses believing several inaccurate myths and mythbusting appears to be a viable tool to address these misconceptions. Teaching Implications: Mythbusting can be implemented within abnormal psychology courses as an an engaging and effective teaching tool, as well as a means to model scientific thinking.